A study of indoor air quality in dormitories of Universiti Malaysia Pahang - Nur Fitriah, Isa (2010)
T he study is all about the findings of air quality recorded in the dormitories of college students Universiti Malaysia Pahang. This concern for the poor quality of air in the room of college students will cause health problems, such as flu, respiratory disorders, fever, and invite many more. In general, there are several factors that lead to changes in the readings on the air quality index in the building. The improper ventilation and aeration system inside the building will as much affects student's daily life. Exposure to bad air quality can cause symptoms of "Sick Building Syndrome" (SBS). This study was carried out based on the hypothesis that ventilation factors, location, temperature and number of occupants that will play an important role in contributing to the effects of air quality of the hostel. The research has been conducted by doing a survey and air quality sampler method.The data has been analysed by using statistics approach. The highest major indoor airborne pollutants from this findings which is recorded without the aid of proper ventilation is Hydrogen Sulphide (H2S) 0.7 ppm, Ammonia gas (NH3 ) 0.4 ppm, Chlorine Gas (C12 ) up to 0.2 ppm and the particulate matter is weighted to 55.15 Lg/M3.To compare with the control data(with the aid of ventilator) the results of using proper ventilation shows a reduction in the reading down to 30%. The highest major indoor airborne pollutants from this findings which is recorded during the daytime is Hydrogen Sulphide (H 2 S) 0.6 ppm, Ammonia gas (NH 3) 0.2 ppm and the particulate matter is weighted to 42.28 JLg/m 3 to compare with the reading during night time which is 38.24 tg/m3 .Major indoor airborne pollutants from this findings which is recorded also gives an exert value when the distance between the dormitories to the cafeteria is relatively low approximately 4.5 in is Hydrogen Sulphide (H 2 S) 0.8 ppm, Ammonia gas (NH 3 ) 0.2 ppm, Chlorine Gas (C12) up to 0.07 ppm, Nitrogen Dioxide (NO2) is 0.06 ppm and the particulate matter is weighted the highest value which is 58.95 jig/rn3 . The highest major indoor airborne pollutants from these findings are recorded when the number of occupant is the high within the populated space. The value of Chlorine Gas (C12) is 0.05 ppm, Ammonia gas (NH 3) 0.8 ppm, Nitrogen Dioxide (NO 2) is 0.04 ppm and Hydrogen Sulphide (14 2 S) is recorded to be 0.8 ppm. Whereas the particulate matter is recorded the highest when the number of occupants is also the highest which is 52.19 jig/M3. We can conclude that the number of occupants, location, type of ventilation system used plays a major part in the reading of indoor air pollutants. There are several parameters were considered to define the actual air quality. Referring to this, an attempt has been made through a study to assess the level of satisfaction regarding the quality of internal environment and healthy living in the study area. Results showed that there are several residential colleges that have indoor air quality environment that is less healthy as a result of certain factors, in particular due to the location and effect of external pollutants.